(3GdJMdjd GdeGdi dGZQGV Jbjje heQGLYI GdGOGA hGdGSJKeGQ aj GdHhQUIs - (3Gejf GdSjO GMeO(B, (3dWais ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2007)
(3gPG GdcJGH jJVef (B: (3GdJMdjd GdeGdj hGdGSGSj Gdafj dCZQGV GdGSJKeGQ aj GdChQGb GdeGdjIq , OhQ eYGjjQ GdeMGSHI aj JYXje LhOI heUOGbjI GdeYdheGJ dGZQGV GdGSJKeGQ EYOGO hYQV GdbhGFe GdeGdjI habG deJWdHGJ cd ef eYGjjQ GdeMGSHI hGdJMdjd GdeGdj , GdJMdjd GdeGdj dCZQGV Jbje GdCOGA GdJGQjNj hEJNGP GdbQGQGJ ,eDTQGJ LhOI GdCSge HGdCSIGb GdeGdjI (B((3GdHhQUI (B) (3GdJMdjd GdeGdj dCZQGV eQGLYI GdCOGA GdJGQjNj , GdJMdjd GdeGdjdCZQGV bjGS heQGLYI GdCOGA GdeSJbHdj hJbjje GdNWWs
Keywords: (3GSJKeGQs; (3GdeMGSHI GdJMdjdjIs; (3HhQUIs; (3SfOGJs